2015
DOI: 10.1063/1.4934966
|View full text |Cite
|
Sign up to set email alerts
|

Black silicon as a platform for bacterial detection

Abstract: Surface-enhanced Raman scattering (SERS) shows promise for identifying single bacteria, but the short range nature of the effect makes it most sensitive to the cell membrane, which provides limited information for species-level identification. Here, we show that a substrate based on black silicon can be used to impale bacteria on nanoscale SERS-active spikes, thereby producing spectra that convey information about the internal composition of the bacterial capsule. This approach holds great potential for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…349 More recently, Hartley et al exploited the needle shape of Au-coated black Si to impale E. coli bacteria and obtained SERS spectra that are not limited to the membrane but extend to internal components. 350 TiO 2 /Metal Hybrids. The combination of plasmonic metal NPs with TiO 2 nanostructures has been explored in many works, borrowing most of the results achieved in research on plasmon-assisted hybrid metal/semiconductor photocatalysts.…”
Section: Dielectrics Decorated With Metals: Synergistic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…349 More recently, Hartley et al exploited the needle shape of Au-coated black Si to impale E. coli bacteria and obtained SERS spectra that are not limited to the membrane but extend to internal components. 350 TiO 2 /Metal Hybrids. The combination of plasmonic metal NPs with TiO 2 nanostructures has been explored in many works, borrowing most of the results achieved in research on plasmon-assisted hybrid metal/semiconductor photocatalysts.…”
Section: Dielectrics Decorated With Metals: Synergistic Effectsmentioning
confidence: 99%
“…In general, the most important hallmarks of metal NP/SiNW hybrid substrates are excellent multiplexing capabilities and high reproducibilities (RSD < 8%).Other very interesting variations are represented by plasmonic NPs anchored to Si nanograss arrays: Talian et al reported a high enhancement factor (∼10 7 –10 8 ) for the detection of R6G and common explosives such as 1,3-dinitrobenzene (1,3-NB) and 2,4-dinitrotoluene (2,4-DNT), as well as good sensitivity toward diterpenoic acids (1.5 mM). , Au-decorated black Si arrays have also been extended to the analysis of single algal cell ( Chlorella vulgaris ) . More recently, Hartley et al exploited the needle shape of Au-coated black Si to impale E. coli bacteria and obtained SERS spectra that are not limited to the membrane but extend to internal components …”
Section: Metal/dielectric Hybrid Interfacesmentioning
confidence: 99%
“…Therefore, it can be used for insertion and SERS identification of bacteria. [46] Li et al designed a structure for the synthesis of Ag NPs on rGO sheets. Owing to the synergistic effect of Ag NPs and rGO, the LOD of E. coli was reduced to 10 5 CFU mL −1 .…”
Section: Enhanced Detection Sensitivitymentioning
confidence: 99%
“…Therefore, it can be used for insertion and SERS identification of bacteria. [ 46 ] Li et al. designed a structure for the synthesis of Ag NPs on rGO sheets.…”
Section: Label‐free Bacterial Detection Using Sersmentioning
confidence: 99%
“…The peculiarities of these mechanisms have been widely reported. (12,13) From established results, it appears that EM field enhancement plays a crucial role in increasing sensitivity, as a strong localized EM field enhances both the molecular scattering and the absorption cross sections. Therefore, recent SERS and SEIRA studies have been focused on the control of EM field intensity by well-defined nano-microstructures.…”
Section: Introductionmentioning
confidence: 99%